Machine learning using robust AI techniques / Prof. Madya Dr. Nordin Abu Bakar - Abu Bakar, Nordin (Prof. Madya Dr.) (2012)
Machine Learning is an area in AI that deals with cognitive ability to assess surrounding area for meaningful actions to pursue. Many algorithms have been applied to aid the assessment process. This research will make use a few AI methods to capture the solution for the robot. The natural environment around us has a lot to offer. From natural resources for the well being of life to the hidden message interactively illustrated by the serenity of the environment. Nature has it all for human beings to live and prosper. One of the branches in computer science is artificiall intelligence; which is an area of research that's looking into natural environment to find a mechanism that might be useful as a tool to solve problems. We are very familiar with speech recognition, for example, that looks into how human creates speech and understands it. Pattern recognition learns how human eyes mechanically capture the image, transmit it to the brain and recognise what the eyes are looking at. The way we think has been imitated in many machine learning algorithms. The ability to think, understand and draw conclusions are human capabilities that have drawn many scientists to devote their life in studying and simulating it for some purpose. Making decisions are one of the learned behaviour that humans tend to be good at or improved through time. How does a person make a right decision ? maybe he learns from past experience or new information he receives. The learning process creates knowledge that guides a person to make the decisions. It is important to know how this process is exercised. There is a model that studies the social behavior of humans called genetic algorithms (GA). An artificial neural network uses brain as a model to map decisions out of several inputs. Others have been looking beyond into the animal kingdom to learn how ants find their way to the food source.